The Sphingolipid Rheostat: A Potential Target for Improving Pancreatic Islet Survival and Function - F. Jessup, Claire; S. Bonder, Claudine; M. Pitson, Stuart; Toby H. Coates, P. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2011)
Beta cell apoptosis and suboptimal islet function are implicated in the development of Type I (T1D) and Type II (T2D) diabetes, as well as the failure of the only current clinical beta cell replacement therapy for T1D, islet transplantation. Sphingosine kinase (SK) is a ubiquitous lipid kinase that controls the balance between prosurvival and proapoptotic precursors (e.g. sphingosine-1-phosphate (S1P) and ceramide, respectively), the so-called 'sphingolipid rheostat', in many cell types. S1P, a potent lipid mediator, acts intracellularly through second messengers and extracellularly through five G-protein coupled receptors (S1P1-5), to promote calcium mobilization, intracellular signaling events, cytoskeleton rearrangements and mitogenesis. SK is important for revascularization responses, regulating the maturation of vascular endothelial progenitors and controlling cellular recruitment. The aim of this review is to highlight the sphingolipid rheostat in pancreatic biology as a therapeutic target for pharmacological and therapeutic intervention for diabetes and islet transplantation. SK and the sphingolipid rheostat are likely to be important for both islet function and beta cell survival and represent a common therapeutic target to protect the beta cell from diabetogenic insults and ultimately improve pancreatic islet function. A number of SK inhibitors and S1P receptor agonists/antagonists (including FTY720 (fingolimod) and its newer derivatives) have been recently described, with some now being used in the clinic. Recent developments in SK biochemistry and islet biology indicate the potential importance of the sphingolipid rheostat in determining islet survival and function. Pharmacological manipulation of this pathway represents a novel therapeutic strategy to prevent diabetes and improve islet transplantation outcomes.
Keywords: diabetes